Factors predicting survival after post‐transplant hepatocellular carcinoma recurrence. Issue 3 (March 2013) - Toso, Christian; Cader, Sonia; Mentha‐Dugerdil, Ariane; Meeberg, Glenda; Majno, Pietro; Morard, Isabelle; Giostra, Emiliano; Berney, Thierry; Morel, Philippe; Mentha, Gilles; Kneteman, Norman M.
Abstract Background Although factors associated with an increased risk of recurrence after liver transplantation for hepatocellular carcinoma (HCC) have been extensively studied, the history of patients with a post‐transplant recurrence is poorly known. Methods Patients experiencing a post‐transplant HCC recurrence from 1996 to 2011 in two transplant programs were included. Demographic, transplant, and post‐recurrence variables were assessed. Results Thirty patients experienced an HCC recurrence—22 men and 8 women with a mean age of 55 ± 6 years. Sixteen (53 %) were outside the Milan criteria at the time of transplantation. Most recurrences (60 %) appeared within the first 18 months after transplantation, ranging between 1.7 and 109 months (median 14.2 months). Mean post‐recurrence survival was 33 ± 31 months. On univariate analysis, total tumor volume (TTV;p = 0.047), microvascular invasion (p = 0.011), and time from transplant to recurrence (p = 0.001) predicted post‐recurrence survival. On multivariate analysis, both time from transplant to recurrence (p = 0.001) and history of rejection (p = 0.043), but not the location of the recurrence or the type of recurrence treatment, predicted post‐recurrence survival. Conclusion This study suggests that patients with early post‐transplant HCC recurrence have worse outcomes. Those with a history of graft rejection have better survivals, possibly due to more active anti‐cancer immunity.